Audio-Based Multi-Door Notification System Using DFPlayer Mini for Automotive Safety - Hamdani; Adi Sastra; Alamsyah Harahap (Journal of Information Technology, computer science and Electrical Engineering, 2025)
Accurate door status detection and notification are essential for guaranteeing passenger safety and mitigating operational risks. Traditional car indicators, such as dashboard lights and basic whistles, offer little contextual information and frequently do not specify which door is ajar. Such constraints diminish the user's situational awareness, particularly when the driver is external to the car or in a cacophonous setting. This study presents an economical, embedded audio notification system for multiple doors, utilizing five normally closed push-button switches, an Arduino Uno microcontroller, a DFPlayer Mini MP3 playback module, an audio amplifier, and an 8-ohm speaker to deliver distinct voice notifications. MP3 messages in the Indonesian language are assigned to each door, facilitating unambiguous and contextually relevant feedback. The experimental findings demonstrate complete detection accuracy across 200 activation cycles. The device exhibits exceptional dependability, minimal power consumption, and straightforward integration, making it suitable for safety upgrades in aftermarket automobiles